Demokrasi dan Kinerja Pers Indonesia - Ngurah Putra, I Gusti (FISIP Universitas Atma Jaya Yogyakarta, 2006)
Abstract: Mass media, especially, press have important rules in the democration process. There are three criteria to evaluate performance of the press. Press as a civic forum, itÃ¢â‚¬â„¢s related to HabermasÃ¢â‚¬â„¢s public sphere that there is space for citizen to discuss about public interest inÃ‚Â the free condition. Press as a watch-dog, that itÃ¢â‚¬â„¢s means press has to protec minority rights from malfuntion of majority power. Press as a mobilization agent, itÃ¢â‚¬â„¢s medium to increase society involment in the politic process.